Uterus couvelaire after caesarean section: A challenging case report - Rendy Singgih; Roy Jansen Sinaga; Yanto Hansitongan Sinaga (Universitas Airlangga, 2021)
HIGHLIGHTS 1. Uterus couvelaire, also known as uteroplacental apoplexy, is one of the causative post-partum haemorrhage and peripartum hysterectomy. 2. The pathophysiology of uterus couvelaire are bleeding in the layer between the decidua-placenta, which then develops and infiltrates into the uterine wall. 3. The uterine couvelaire is associated with placental abruption, placenta previa, coagulopathy, pre-eclampsia, uterine rupture, and amniotic fluid embolism. 4. This case report shows the unknown of causative during delivery which can lead to maternal morbidity even mortality if there is no proper maternal monitoring during delivery. ABSTRACT Objectives: To discuss the discovery of uterine couvelaire events after the cesarean section without accompanying placental abruption. Case Report: Uterus Couvelaire is a rare occurrence. The incidence of this case is difficult to ascertain and its estimated incidence is as much as 20% and others' estimatation is as low as 5%. It occurs mainly due to complications from placental abruption. When a vascular injury occurs in the placenta, it causes bleeding that infiltrates the wall of the uterus. This case is usually diagnosed accidentally because it is diagnosed only by direct visualization or biopsy. In this case, uterine couvelaire was found in a woman after a cesarean section that had been performed previously. Uterine couvelaire events are usually seen due to complications from placental abruption, but in this case, there was none. Conclusion: It was not known for sure what caused the emergence of the uterine couvelaire in this case. Hysterectomy was performed in this case due to the patient's unstable hemodynamic state.